Merocyanines for vacuum-deposited small-molecule organic solar cells - Chen, Ko-Wei; Huang, Chong-Wei; Lin, Shao-Yu; Liu, Yi-Hung; Chatterjee, Tanmay; Hung, Wen-Yi; Liu, Shun-Wei; Wong, Ken-Tsung (Organic electronics, 2015)
[Display omitted] •Three merocyanines were synthesized and characterized as electronic donor for SMOSCs.•The physical properties correlate to the e-donating groups and intermolecular interactions.•The PCE is limited by the hole mobility, DPPT-based device achieved a PCE of 3.52%. We report here synthesis and photovoltaic properties of three merocyanines dyes (DPPT, DTPT, 1-NPPT) which are functionalized with electron withdrawing thiazolidenemalononitrile and electron rich diarylamine functionalities. It is found that structural feature of the diarylamino groups has a profound effect on the physical properties such as the absorption spectrum, oxidation potential, and HOMO/LUMO energy levels. The compound DTPT containing a better electron-donating ditolyl group, exhibits red-shifted absorption with relatively higher molar extinction coefficient, indicating its better light-harvesting ability. Hole mobility of these compounds is found to be strongly dependent on the various intermolecular interactions. Interestingly, single crystal structures reveal that the crystal packing motifs are rather closely related to the observed hole mobility in a trend of DPPT>DTPT>1-NPPT. Vacuum-processed small-molecule organic solar cells were fabricated using the title merocyanines as p-type materials (donor) in combination with fullerene (C60 or C70) as n-type material (acceptor) with various device configurations. Among them, the DPPT-based devices outperform the devices based on DTPT and 1-NPPT. The power conversion efficiency (PCE) of DPPT-based device was improved from 1.55% of a BHJ device to 2.63% of a PMHJ device and 3.52% of a PMHJ device without the thin donor layer.